The Effect of Solvent and Amine Concentration on the Modification of Silica Sand Waste by Grafting Method as an Adsorbent - Dominica Edora Stella Raharjanto; Dwi Ana Anggorowati; Nanik Astuti Rahman (Universitas Islam Raden Rahmat, Malang, 2025)
Industrial waste is all types of waste materials or residual materials originating from the results of an industrial process. One of the industrial wastes in solid form is silica sand waste from the sandblasting process which has the potential to be used as a source of silica for adsorbents. This experiment is conducted to determine the type of solvent and the best addition volume of APTES in silica modification using amine (APTES). The process used in this experiment is a grafting process, where silica goes through a reflux process with solvents and APTES so that the amine groups attach to the surface of the modified silica. The results of the experiment is analysed using TGA and FTIR, and shows that the most optimal addition volume of APTES is 5 mL with the best types of solvents being ethanol and toluene solvents with the amount of amine loading contained in the modified silica being 1,9430 and 5,2552 mmol g aminopropyl/gram silica, respectively, but not in water solvents. The results of this study shows a successful APTES grafting of modified silica which can be used as an adsorbent for CO2 capture.